Los proyectos de colonización bajo el Segundo Imperio y el fortalecimiento del Estado mexicano - Sánchez, Evelyne (El Colegio de México, A.C., 2013)
Even though it was considered a priority soon after independence, the colonization policy did not receive a strong governmental support until the age of Porfirio Díaz. During the Second Empire, however, the Ministry of Economy showed a great determination to implement this policy, which tends to strengthen the idea that Maximilian's Empire was a period of acceleration in the Mexican State construction process prior to the Porfiriato and, on the other hand, that his policy, implemented by a first-class cabinet, was inscribed within the continuity of the projects designed during the Reform period. The analysis of a number of cases located in the district of Córdoba, Veracruz, shows both the strategic interest that this area held for the Empire and the strategies developed by the Ministry of Economy in order to retain control over these projects in spite of the local interests involved.